Continuous local anaesthetic wound catheter infiltration after clamshell thoracotomy. Issue 1 (28th March 2019) - Lan‐Pak‐Kee, V.; Egan, T.; Tarrell, T.; Konig, T.
Summary: We report on the novel and successful use of local anaesthetic wound infusions via elastomeric pumps in a 17‐year‐old male who underwent emergent clamshell thoracotomy after sustaining a stab wound to the flank. This formed one component of a multi‐modal analgesic regimen aimed at reducing opioid requirements and their associated side‐effects. The patient was mobilising and was discharged from the intensive care unit 24 h postoperatively. There was an unplanned break in the local anaesthetic infusion during which the patient's reported pain scores increased significantly. The catheters were removed on the fifth postoperative day and he was discharged from hospital on day 7.